Co‐activation pattern alterations in autism spectrum disorder–A volume‐wise hierarchical clustering fMRI study. Issue 6 (16th May 2021) - Paakki, Jyri‐Johan; Rahko, Jukka S.; Kotila, Aija; Mattila, Marja‐Leena; Miettunen, Helena; Hurtig, Tuula M.; Jussila, Katja K.; Kuusikko‐Gauffin, Sanna; Moilanen, Irma K.; Tervonen, Osmo; Kiviniemi, Vesa J.
Abstract: Introduction: There has been a growing effort to characterize the time‐varying functional connectivity of resting state (RS) fMRI brain networks (RSNs). Although voxel‐wise connectivity studies have examined different sliding window lengths, nonsequential volume‐wise approaches have been less common. Methods: Inspired by earlier co‐activation pattern (CAP) studies, we applied hierarchical clustering (HC) to classify the image volumes of the RS‐fMRI data on 28 adolescents with autism spectrum disorder (ASD) and their 27 typically developing (TD) controls. We compared the distribution of the ASD and TD groups' volumes in CAPs as well as their voxel‐wise means. For simplification purposes, we conducted a group independent component analysis to extract 14 major RSNs. The RSNs' average z ‐scores enabled us to meaningfully regroup the RSNs and estimate the percentage of voxels within each RSN for which there was a significant group difference. These results were jointly interpreted to find global group‐specific patterns. Results: We found similar brain state proportions in 58 CAPs (clustering interval from 2 to 30). However, in many CAPs, the voxel‐wise means differed significantly within a matrix of 14 RSNs. The rest‐activated default mode‐positive and default mode‐negative brain state properties vary considerably in both groups over time. This division was seen clearly when the volumes were partitioned into two CAPs and then further examined along the HC dendrogram of the diversifying brain CAPs. The ASD group network activations followed a more heterogeneous distribution and some networks maintained higher baselines; throughout the brain deactivation state, the ASD participants had reduced deactivation in 12/14 networks. During default mode‐negative CAPs, the ASD group showed simultaneous visual network and either dorsal attention or default mode network overactivation. Conclusion: Nonsequential volume gathering into CAPs and the comparison of voxel‐wise signal changes provide a complementary perspective to connectivity and an alternative to sliding window analysis. Abstract : Co‐activation patterns (CAPs) of resting state brain activity varyingly contain both default mode network (DMN)‐positive and default mode network‐negative brain state properties. With hierarchical clustering, they can be divided into shorter substates. When applied in autism spectrum disorder, this method showed simultaneous visual network and either dorsal attention or DMN overactivation during DMN‐negative CAPs. Nonsequential volume gathering into CAPs provides an alternative to sliding window analysis.